Financial Performance Analysis of PT. Hero Supermarket Tbk During the Period of Economic Slowdown - Rifqi, Audi; Damayanti, Sylviana Maya (Journal of Business and Management, 2017)
AbstractIndonesia is 4th most populated nation in 2015, with emerging middle class consumers that has growing interest in consumer products. Household consumption expenditures contributed 56.07% to the nation GDP in 2014. This makes retail industry a promising business in Indonesia. During the period of 2011-2015, Indonesia economic growth was experiencing a slight slowdown, which impacts the retailer in Indonesia. With low GDP growth, retail industry in Indonesia as one of the biggest contributor to GDP needs to maintain the performance to leverage the nation economy. The retail sales trend was fluctuating within each year, as consumer curbed spending, saving money as they know the unstable economic condition. One of the oldest local modern retail that still existed until now is PT Hero Supermarket Tbk. Having a declining market trend, PT Hero Supermarket Tbk seems getting hit by the effect of economic slowdown that drive the declining of retail sales. By the end of 2015, the company experienced loss even though it has done several preventive measures such as closing some less profitable store, driven by the previous yearâ€™s performance. This research will assess the financial performance of PT Hero Supermarket Tbk within the year 2011-2015, when the nation and the industry experienced hardship as the effect from economic slowdown. The research will be using financial ratio analysis and DuPont system of analysis. Three types of analysis will be used which are time series analysis, cross section analysis, and combined analysis. The result of this research shows the performance of PT Hero Supermarket Tbk is averagely declining from 2011-2015. The ratios of PT Hero Supermarket Tbk is below industry average. The last two years were the worst year within the period for PT Hero Supermarket Tbk. The recommendation for PT Hero Supermarket Tbk is to improve its operating efficiency and asset-use efficiency to increase its ROA and ROE. It can be done by reducing the operating cost, especially rent and salaries, as both contribute the most to the operating expense. PT Hero Supermarket Tbk shouldÂ Keywords: Financial, Indonesia, performance, ratio, retail